The Effect of Inquiry Learning Method by Using Laboratory and Logical Thinking on Learning Outcome in Chemical Reaction Rate - Gulmah Sugiharti; Siti Kholilah Hasibuan (Pascasarjana Universitas Negeri Medan, 2017)
Abstract: This research aims to discover the effect of learning models using laboratory and logical thinking ability to the students of chemistry learning outcomes on the material rate of the reaction. The research was conducted on the students of class XI IPA MAN 2 Model Medan T. A. 2016/2017. The population in this research is all students of class XI IPA MAN 2 Model Medan which consists of 8 classes. The sample is determined by purposive sampling that takes 2 classes that made the experimental class. This type of research is experimental type with factorial design 2 x 2. Data retrieval for student learning outcomes obtained by test of learning result using valid instrument as much as 23 questions and reliable (0,875). Whereas, the data for students logical thinking ability is obtained through questionnaire of logical thinking ability by using valid instrument data. Data analysis techniques used two-way variance analysis. The result of research shows that there is influence of Inquiry learning model by using real laboratory and virtual laboratory on students' chemistry learning result on reaction rate material with Fcount> Ftable that is 28,6367> 3,99, there is influence of high logical thinking ability and low logical thinking ability to the result of student's chemistry learning on the material of reaction rate with Fcount> Ftable is 21,6251> 3,99, and there is interaction between learning model with logical thinking ability to student's chemistry learning on reaction rate material with Fcount> Ftable that is 20,7645 > 3.99. Keywords: learning outcomes, interaction, virtual laboratory, real laboratory, inquiry learning model